Evaluation of a suspended radiation protection system to reduce operator exposure in cardiology interventional procedures. Issue 5 (4th August 2021) - Zanca, Federica; Dabin, Jérémie; Collard, Celine; Alexandre, Nicolas; De Groote, Alicia; Salembier, Jean Paul; Henry, Michel; Rombaut, Emmanuel; Sghaier, Sonia; Massart, Pierre‐Emmanuel
Abstract: Objectives: To investigate a novel suspended radiation shield (ZG), in reducing operator radiation exposure during cardiology interventions. Background: Radiation exposure to the operator remains an occupational health hazard in the cardiac catheterization laboratory. Methods: An anthropomorphic mannequin simulating an operator was placed near a phantom, simulating a patient. To measure the operator dose reduction, thermoluminescent detectors (TLDs) were inserted into the head and into the eye bulbs of the mannequin, while electronic dosimeters were positioned on the temple and at the level of the thyroid. Measurements were performed without and with the ZG system in place. Physician exposure was subsequently prospectively measured on the torso, on the left eye and on upper arm using the same electronic dosimeters, during clinical procedures (coronary angiography (CA) and percutaneous coronary intervention (PCI)). The physicians dose reduction was assessed by comparing operator dose when using traditional radioprotection garments (Phase 0) versus using the ZG system (Phase 1). Results: Dose reductions as measured on the mannequin ranged from 66% to the head, to 100% to the torso. No dose was detected at the level of the torso and thyroid with ZG. When comparing CA and PCI procedures between Phase 0 and Phase 1, a significant difference ( p  < 0.001) was found for the left eye and the left wrist. Dose reduction as measured during clinical procedures for left eye/upper arm were on average 78.9%/95.6% for CA and 83.0%/93.0% for PCI, respectively ( p  < 0.001 for both). Conclusions: The ZG systems has a great potential to significantly reduce operator dose through the creation of a nearly zero‐radiation work environment.